2013
DOI: 10.1186/1471-2334-13-334
|View full text |Cite
|
Sign up to set email alerts
|

Association of RSV-related hospitalization and non-compliance with Palivizumab among commercially insured infants: a retrospective claims analysis

Abstract: BackgroundPalivizumab has been shown to decrease the incidence of hospitalization due to respiratory syncytial virus (RSV) in infants at risk of severe RSV disease. We examined the association between compliance with palivizumab dosing throughout the RSV season and risk of RSV-related hospitalization in clinical practice.MethodsSubjects who were born and discharged from the hospital before the RSV season and received ≥1 palivizumab dose during their first RSV season were identified from a large US commercial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…These results were also observed in 2 recent retrospective cohort studies evaluating outcomes in insurance claims databases during the 6 RSV seasons between 2003–2004 and 2008–2009 24 , 25 …”
Section: Clinical Impact Of Full-season Dosing Vs Missed or Delayed supporting
confidence: 62%
“…These results were also observed in 2 recent retrospective cohort studies evaluating outcomes in insurance claims databases during the 6 RSV seasons between 2003–2004 and 2008–2009 24 , 25 …”
Section: Clinical Impact Of Full-season Dosing Vs Missed or Delayed supporting
confidence: 62%
“…One study conversely found that RSV hospitalizations were more frequent before the initiation of palivizumab dosing (including outpatient dosing) for the season. 20 This may be a product of a difference in inpatient and outpatient patterns of palivizumab initiation or that the population of children' s hospitals studied in PHIS may not be representative of the overall population. While we do not know when outpatient palivizumab dosing began in relationship to our study, it is possible that inpatient providers (compared with those in the outpatient setting) are more familiar with RSV hospitalization patterns and use these patterns when dosing palivizumab to inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Although there is no RSV vaccine, certain children at high risk are given prophylaxis with palivizumab, an RSV monoclonal immunoglobulin, which can reduce RSV hospitalizations. 19,20 The latest policy statement from the American Academy of Pediatrics (AAP) recommends that palivizumab administration for these children at high risk begins at the start of regional activity season. 21 One study found that using RSV regional activity data to determine when to initiate prophylaxis rather than using a set initiation date (November) would increase protection by 15%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that the Palivizumab® does not just prevent HRSV infection but also decreases the hospitalization occurrence [12], and in fact, only one of our study group was hospitalized. Despite the recognized importance of Palivizumab® prophylaxis, in our study 17.4% of children were infected by HRSV.…”
Section: Discussionmentioning
confidence: 62%